MAGNETORESISTANCE in La0.1Ca0.9MnO3 - Gunarto, Y.E.; Kurniawan, B.; Poertadji, S.; Steven, E. (Jurnal Spektra, 2015)
AbstractWe have performed measurements of resistivity as a function of temperature with a certain large external magnetic field and resistivity as a function of the external magnetic field in room temperature conditions for L0.1C0.9MnO3 compound. Measurement of resistivity as a function of temperature using quantum squid design is done at a temperature of 8-80 K with an external magnetic field variation of 0, 3, 6, and 8.5 Tesla. The resistivity measurements as a function of the external magnetic field from 0 to 0.7600 Tesla performed at room temperature using a four-point probe. At the same temperature, the greater the external magnetic field, the greater its magnetoresistance. For the same external magnetic field, increasing the temperature will decrease magnetoreistance.Keywords: external magnetic field, squid quantum, magnetoresistanceÂ AbstrakTelah kami lakukan pengukuran terhadap resistiviti sebagai fungsi suhu dengan besar medan magnet luar tertentu dan juga resistiviti sebagai fungsi medan magnet luar dalam kondisi suhu ruang untuk senyawa L0,1C0,9MnO3. Pengukuran resistivitas sebagai fungsi suhu menggunakan squid quantum desain dilakukan pada suhu 8-80 K dengan variasi medan magnet luar 0, 3, 6, dan 8,5 Tesla. Pengukuran resistivitas sebagai fungsi medan magnet luar dari 0-0,7600 Tesla dilakukan pada suhu ruang. Pada suhu yang sama, semakin besar medan magnet luar, maka semakin besar magnetoresistansi nya. Untuk medan magnet luar yang sama, semakin bertambah suhunya maka magnetoreistansi akan semakin berkurang.Katakunci: medan magnet luar, squid quantum, magnetoresistansiÂ